1 − x + x 2 − x 3 + … + x 1 6 − x 1 7 The polynomial above may be written in the form a 0 + a 1 y + a 2 y 2 + . . . + a 1 6 y 1 6 + a 1 7 y 1 7 where y = x + 1 and a i ′ s are constants. Find a 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Good observation with the "generating functions" manipulation.
Let f ( x ) = 1 − x + x 2 + . . . + x 1 6 − x 1 7 . This expression is the sum of the first 18 terms of a geometric sequence whose first term is 1 and common ratio − x . Therefore, f ( x ) = 1 − ( − x ) 1 − ( − x ) 1 8 = 1 + x 1 − x 1 8 for x = − 1 ( ∗ ) In the other hand, if f ( x ) = a 0 + a 1 ( x + 1 ) + a 2 ( x + 1 ) 2 + . . . + a 1 6 ( x + 1 ) 1 6 + a 1 7 ( x + 1 ) 1 7 , then differentiating both sides twice and evaluating at x = − 1 , we get f ′ ′ ( − 1 ) = 2 a 2 . Now using ( ∗ ) and L'hopital Rule three times, we get that 2 a 2 = x → − 1 lim d x 2 d 2 1 + x 1 − x 1 8 = 1 6 3 2 . Then a 2 = 8 1 6 .
The last part, where we find the second derivative of the function 1 + x 1 − x 1 8 and apply L'hopital can be a tedious procedure. So another way of finding the value of f ′ ′ ( − 1 ) is the following. We can differentiate the equality f ( x ) = ∑ n = 0 n = 1 7 ( − 1 ) n x n twice, so we get f ′ ′ ( x ) = ∑ n = 2 1 7 ( − 1 ) n n ( n − 1 ) x n − 2 . Evaluating at x = − 1 , f ′ ′ ( − 1 ) = n = 2 ∑ 1 7 n ( n − 1 ) = n = 1 ∑ 1 7 n 2 − n = 1 ∑ 1 7 n = 6 1 7 ( 1 7 + 1 ) ( 2 ( 1 7 ) + 1 ) − 2 1 7 ( 1 7 + 1 ) = 1 6 3 2 .
This is beautifulllll!!!!
I did exactly the same way as the second part of your solution sir..
x = y − 1 f ( x ) = 1 − x + x 2 − x 3 + . . . + x 1 6 − x 1 7 = 1 − ( y − 1 ) + ( y − 1 ) 2 − ( y − 1 ) 3 . . . + ( y − 1 ) 1 6 − ( y − 1 ) 1 7
Note that the coefficient of the y 2 term in the expansion of each power of ( y − 1 ) is equal to ( − 1 ) n ( 2 n ) , where n is the power of ( y − 1 ) . And since the sign of each odd power of ( y − 1 ) is negative, all y 2 terms in f ( y − 1 ) are positive, and a 2 is their sum. Thus,
a 2 = n = 1 ∑ 1 7 ( 2 n ) = ( 2 ) ( 1 ) ( 1 7 ) ( 1 6 ) + ( 1 6 ) ( 1 5 ) + ( 1 5 ) ( 1 4 ) + . . . + ( 3 ) ( 2 ) + ( 2 ) ( 1 ) = 2 ( 1 6 ) ( 1 7 + 1 5 ) + ( 1 4 ) ( 1 5 + 1 3 ) + . . . + ( 2 ) ( 3 + 1 ) = 1 6 2 + 1 4 2 + . . . + 2 2 = 4 n = 1 ∑ 8 n 2 = 4 6 ( 8 ) ( 9 ) ( 1 7 ) = 8 1 6
Yes, this would be the "brute force" approach to evaluating the coefficients.
Problem Loading...
Note Loading...
Set Loading...
f ( x ) = 1 − x + x 2 − x 3 + . . . + x 1 6 − x 1 7 x f ( x ) = x − x 2 + x 3 − . . . − x 1 8 Adding these two we get ( 1 + x ) f ( x ) = 1 − x 1 8 f ( x ) = f ( y − 1 ) = 1 + ( y − 1 ) 1 − ( y − 1 ) 1 8 = y 1 − ( y − 1 ) 1 8 a 2 is equal to coefficient of y 3 in the expansion of 1 − ( y − 1 ) 1 8 i,e, a 2 = ( 3 1 8 ) = 8 1 6